Double-site supported noble metal catalyst as well as preparation method and application thereof

By using a two-site supported precious metal catalyst in the PEM electrolytic catalyst and using hydrophilic oxides with hydroxyl-rich surface to support precious metals, the problem of poor performance of existing catalysts under operating conditions is solved, and efficient electrolytic water generation and cost reduction effects are achieved.

CN119549146AActive Publication Date: 2025-03-04TAN KAH KEE INNOVATION LAB
View PDF 10 Cites 0 Cited by

Patent Information

Application Number
CN202411803978.1
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-12-09
Publication Date
2025-03-04
Estimated Expiration
2044-12-09

AI Technical Summary

Technical Problem

The existing PEM electrolytic catalysts perform poorly under actual operating conditions, mainly because the ionomer adsorption sites are not effectively constructed, resulting in the catalyst active sites being covered, affecting performance expression.

Method used

A two-site supported precious metal catalyst is used to support active precious metals by hydrophilic oxides with hydroxyl-rich surfaces as support. The hydroxyl site on the surface of the support is used as a strong adsorption site of the ionomer to promote the exposure of precious metals and improve the performance expression of active sites.

Benefits of technology

By segmenting the ionomer adsorption sites and active sites, the performance expression and utilization of the catalyst are improved, the charge transfer impedance is reduced, and the electrolytic efficiency and cost-effectiveness of PEM electrolytic water is improved.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119549146A_ABST
    Figure CN119549146A_ABST
Patent Text Reader

Abstract

The invention provides a double-site supported noble metal catalyst as well as a preparation method and application thereof, and relates to the technical field of proton exchange membrane electrolyzed water. The double-site supported noble metal catalyst comprises a noble metal oxide and a hydrophilic oxide coated in the noble metal oxide, wherein the surface of the hydrophilic oxide is rich in hydroxyl. According to the invention, by constructing a double-site synergistic reaction anode catalyst structure, an ionomer adsorption site and an active site are segmented, the exposure of the active site is improved, a stable proton transmission channel is constructed, and finally, the catalyst utilization rate and the electrolytic efficiency are improved through an efficient and stable catalyst / ionomer interface; and the cost of the proton exchange membrane electrolyzed water anode catalyst is reduced.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to the technical field of proton exchange membrane water electrolysis, and in particular to a dual-site supported noble metal catalyst and a preparation method and application thereof. Background Art

[0002] Proton exchange membrane water electrolysis (PEMWE) has become a key technology for green hydrogen production due to its high energy conversion efficiency, fast response speed, high-purity hydrogen production, and clean and pollution-free advantages. It is widely used in energy storage, transportation, industrial production and other fields. Membrane electrode (MEA) is one of the core components of PEM water electrolysis hydrogen production technology, usually composed of proton exchange membrane (PEM), catalyst layer (CL) and porous transport layer (PTL).

[0003] The catalyst layer is the core site of electrochemical reactions for multiphase material transport and energy conversion, and is crucial for hydrogen production by PEM water electrolysis. The electrochemical performance and stability of the catalyst layer mainly depend on the constructed electrode interface structure, namely the catalyst / ionomer interface, which requires balancing the proton, electron and water / gas transport processes at the same time. Among them, the ionomer is not only responsible for bonding the catalyst particles to form a stable electrode as a binder, but also plays an important role as a proton channel as a solid electrolyte. Excessive ionomer adsorption will cause the active sites of the catalyst to be covered, causing "poisoning" and hindering the effective transmission of the reaction gas products. Too little ionomer adsorption will affect the performance expression due to the lack of proton channels, and due to insufficient mechanical strength, it is difficult to maintain long-term stable operation under working conditions. How to balance the ionomer adsorption sites on the catalyst surface and the kinetic reaction active sites is the key to achieving efficient utilization of PEM water electrolysis catalysts. The existing pursuit of a single active site can no longer meet the above-mentioned complex interface reaction requirements, and it is urgent to develop and design new catalyst structures to meet the dual-site working conditions.

[0004] Existing research on PEM anode catalysts has focused on the development of active sites, and a variety of solutions have been proposed. For example: increasing the number of active sites by optimizing the morphology and structure; adjusting the electronic structure of active sites by atomic doping to improve activity; improving the dispersion of precious metals by carrier loading, and improving catalyst activity and stability through metal-carrier interactions. These strategies all focus on optimizing the active sites of catalysts, but they often have little effect when applied to actual working conditions. The main reason is that they ignore the effective construction of ionomer adsorption sites and lack the "switch" to express the working conditions of active sites.

[0005] CN116925576A discloses a relatively simple carbon carrier modification method, which is mainly optimized by controlling the morphology of the carrier, and by modifying the carbon carrier with small molecule organic acid, the anchoring efficiency of the precious metal Pt in the pore is increased, and the ionomer poisoning is reduced. However, the above method still cannot avoid the poisoning effect of the ionomer on the catalyst, and the ionomer will inevitably be ingested into the pores, accompanied by the serious poisoning phenomenon of the Pt nanoparticles on the outer surface. In addition, the preparation of mesoporous carbon carriers is relatively cumbersome, and is accompanied by a large amount of post-processed sewage, and cannot form mass production.

[0006] CN116613326A discloses a method for preparing a membrane electrode by printing different catalyst layers in layers. The method adjusts the process of electrode preparation, and the inkjet printing ink of the catalyst layer is composed only of a solvent and a catalyst. By constructing a three-phase reaction interface from a macroscopic perspective, the catalyst is prevented from being poisoned by ionomers. However, the macroscopic interface of ionomer / catalyst still exists in the catalytic layer prepared by the method, and the poisoning effect of ionomers on Pt catalysts cannot be avoided. At the same time, the operation of inkjet printing is complicated, which is not conducive to large-scale preparation.

[0007] CN115786974A discloses a catalyst for water electrolysis and a preparation method thereof, wherein a catalyst precursor is obtained by the method, wherein the catalyst precursor comprises a carrier precursor and a noble metal oxide precursor loaded thereon, wherein the carrier precursor is a non-noble metal inorganic oxide carrier; and during the preparation process, the catalyst precursor is first post-treated to form oxygen vacancies on both the carrier precursor and the noble metal oxide precursor; and the post-treatment step comprises annealing in an ammonia atmosphere.

[0008] The above design ideas do not fundamentally solve the problem of ionomer adsorption. They only limit the problem of ionomer poisoning through physical isolation or process adjustment, lacking molecular-level chemical thinking. At the same time, the operation process is relatively complicated and lacks the possibility of scaled-up production. At the same time, PEM water electrolysis and fuel cells have different operating conditions, and more complex interface reactions and hydrothermal effects need to be considered.

[0009] In view of this, the present invention is proposed. Summary of the invention

[0010] The purpose of the present invention is to provide a dual-site supported noble metal catalyst and its preparation method and application. The dual-site supported noble metal catalyst of the present invention uses a hydrophilic oxide with rich hydroxyl groups on the surface as a carrier to load active noble metals, and uses the hydroxyl sites on the surface of the carrier as strong adsorption sites of ionomers to promote the exposure of active noble metals and improve the performance expression of active sites.

[0011] In order to achieve the above-mentioned purpose of the present invention, the following technical solutions are particularly adopted:

[0012] In a first aspect, the present invention provides a dual-site supported precious metal catalyst, wherein the dual-site supported precious metal catalyst comprises a precious metal oxide and a hydrophilic oxide having a hydroxyl-rich surface and coated in the precious metal oxide.

[0013] Preferably, the noble metal oxide is selected from any one of ruthenium oxide, rhodium oxide, iridium oxide or platinum oxide, or a combination of at least two thereof, preferably iridium oxide.

[0014] Preferably, the loading amount of the noble metal oxide is 10 to 70 wt %.

[0015] Preferably, the hydrophilic oxide includes any one of titanium oxide, niobium oxide, tin oxide or silicon oxide, or a combination of at least two thereof.

[0016] Preferably, the particle size of the hydrophilic oxide is 10 nm to 1 μm.

[0017] Preferably, the content of hydroxyl groups in the hydrophilic oxide with rich hydroxyl groups on the surface is 25-75% (the content here refers to the ratio of the statistical hydroxyl signal to the total oxygen signal on the surface after the mass spectrometry peak signal test of H2O).

[0018] Preferably, the hydrophilic oxide with rich surface hydroxyl groups is prepared by the following steps:

[0019] The hydrophilic oxide is immersed in a modification solution, and then washed and dried to obtain the hydrophilic oxide with rich hydroxyl groups on the surface; wherein the modification solution includes any one of hydrogen peroxide, a strong base, and a catalyst for Fenton reaction, or a combination of at least two thereof.

[0020] Preferably, the strong base includes any one of sodium hydroxide, potassium hydroxide, lithium hydroxide, cesium hydroxide or rubidium hydroxide, or a combination of at least two thereof.

[0021] Preferably, the Fenton reaction catalyst comprises any one of ferrous chloride, ferrous nitrate or ferrous sulfate, or a combination of at least two thereof.

[0022] Preferably, the mass percentage of the hydrophilic oxide in the modified solution is 0.5-5%.

[0023] Preferably, the soaking temperature is 70-90° C., and the soaking time is 20-120 min.

[0024] Preferably, the mass percentage of hydrogen peroxide in the modified solution is 3-30%.

[0025] Preferably, the mass percentage of the strong base in the modified solution is 1-25%.

[0026] Preferably, the mass percentage of the Fenton reaction catalyst in the modified solution is 5 to 50%.

[0027] In a second aspect, the present invention provides a method for preparing a dual-site supported noble metal catalyst as described in the first aspect, wherein the method for preparing a dual-site supported noble metal catalyst comprises the following steps:

[0028] (1) ultrasonically dispersing a hydrophilic oxide having a rich surface hydroxyl group into an alcohol solution, adding a precursor solution of a precious metal dropwise, stirring and drying to obtain a solid mixture;

[0029] (2) mixing and grinding the molten salt and the solid mixture obtained in step (1) to obtain a ground product;

[0030] (3) calcining the ground product obtained in step (2) to obtain a calcined product; then ultrasonically dispersing the calcined product into an aqueous solution, centrifugally washing it with water, and then drying and grinding it to obtain the dual-site supported precious metal catalyst.

[0031] Preferably, in step (1), the mass ratio of the metal element and the noble metal precursor in the hydrophilic oxide having a hydroxyl-rich surface is 1:(0.15-3.35).

[0032] Preferably, in step (1), the mass volume ratio of the hydrophilic oxide with rich surface hydroxyl groups to the alcohol solution is 1 g: (100-150) mL.

[0033] Preferably, in step (1), in the precursor solution of the noble metal, the mass volume ratio of the metal precursor to the alcohol solution is 1 g: (10-50) mL.

[0034] Preferably, in step (1), the alcohol solution is isopropanol.

[0035] Preferably, in step (1), the precursor of the precious metal comprises any one of chlororuthenic acid, chlororhodic acid, chloroiridic acid, ruthenium trichloride, iridium acetate, iridium acetylacetonate or chloroplatinic acid, or a combination of at least two thereof.

[0036] Preferably, in step (1), the stirring temperature is 40 to 60° C., and the stirring time is 1 to 3 hours.

[0037] Preferably, in step (1), the drying temperature is 60 to 90° C., and the drying time is 3 to 5 hours.

[0038] Preferably, in step (2), the mass ratio of the molten salt to the solid mixture is (1.43-19.14):1, preferably (4.78-19.14):1.

[0039] Preferably, in step (2), the grinding speed is 100 to 300 rpm, the grinding time is 0.5 to 2 h; and the particle size of the grinding product obtained by the grinding is 300 to 500 nm.

[0040] Preferably, in step (3), the calcination temperature is 250-450° C., the calcination time is 0.5-2 h, and the calcination heating rate is 5-15° C. / min.

[0041] Preferably, in step (3), the number of centrifugal washing is 3 to 6 times.

[0042] Preferably, in step (3), the drying temperature is 60 to 80° C., and the drying time is 4 to 6 hours.

[0043] Preferably, in step (3), the grinding speed is 100 to 300 rpm, and the grinding time is 0.5 to 2 h.

[0044] Preferably, in step (3), the particle size of the dual-site supported noble metal catalyst is 10 nm to 1 μm.

[0045] In a third aspect, the present invention provides a use of a dual-site supported noble metal catalyst as described in the first aspect in the preparation of an anode catalyst for PEM water electrolysis, a membrane electrode for PEM water electrolysis, or an electrolytic cell for PEM water electrolysis.

[0046] In a fourth aspect, the present invention provides a membrane electrode for PEM water electrolysis, comprising a proton exchange membrane and an anode catalyst layer and a cathode catalyst layer arranged on both sides of the proton exchange membrane; wherein the anode catalyst layer comprises a dual-site loaded precious metal catalyst as described in the first aspect.

[0047] Preferably, the loading of the noble metal element in the anode catalyst layer is 0.100-1.000 mg / cm 2 .

[0048] Preferably, the anode catalyst layer further comprises an ionomer.

[0049] Preferably, the ionomer comprises any one of perfluorosulfonic acid, sulfonated polyetheretherketone resin or sulfonated trifluorostyrene resin or a combination of at least two thereof, preferably perfluorosulfonic acid.

[0050] Preferably, the loading of the noble metal element in the cathode catalyst layer is 0.100-1.000 mg / cm 2 .

[0051] Preferably, the proton exchange membrane is a 115 proton exchange membrane.

[0052] In a fifth aspect, the present invention provides a method for preparing a membrane electrode for PEM water electrolysis according to the fourth aspect, the method for preparing a membrane electrode for PEM water electrolysis comprising the following steps:

[0053] The dual-site supported noble metal catalyst, ionomer solution, water and alcohol are mixed, stirred and dispersed, and degassed after ball milling to obtain an anode catalyst layer slurry;

[0054] Applying the anode catalyst layer slurry to one side of the transfer substrate, and after drying, forming the anode catalyst layer;

[0055] Applying the cathode catalyst layer slurry to the other side of the transfer substrate, and after drying, forming the cathode catalyst layer;

[0056] The anode catalyst layer and the cathode catalyst layer are respectively transferred to both sides of the proton exchange membrane by hot pressing transfer to obtain the PEM membrane electrode for water electrolysis.

[0057] Preferably, the dual-site supported noble metal catalyst accounts for 15-40% of the total mass of the anode catalyst layer slurry.

[0058] Preferably, the ionomer solution is 5-40% of the mass of the dual-site supported noble metal catalyst.

[0059] Preferably, the solid content of the ionomer solution is 15-20 wt%.

[0060] Preferably, the alcohol is a C1-C8 monohydric liquid alcohol and / or a C1-C8 polyhydric liquid alcohol.

[0061] Preferably, the alcohol is selected from any one of ethanol, n-propanol, isopropanol or propylene glycol, or a combination of at least two thereof.

[0062] Preferably, the mass ratio of water to alcohol is (5-8):(2-5).

[0063] Preferably, the ball milling conditions include: 2.0-4.5 mm ZrO2 ball milling beads, constant temperature ball milling at 15-25°C, a rotation speed of 300-1000 rpm, and a time of 2-12 hours.

[0064] In a sixth aspect, the present invention provides an electrolytic cell for PEM water electrolysis, wherein the electrolytic cell for PEM water electrolysis comprises the membrane electrode for PEM water electrolysis described in the fourth aspect.

[0065] Compared with the prior art, the present invention has the following beneficial effects:

[0066] (1) When the dual-site supported noble metal catalyst of the present invention is used in a device, the charge transfer impedance is reduced by 30%, proving its performance improvement. At the same time, the high current density (6.0 A / cm 2 ) working conditions, the performance increased by 266 mV, proving the high operating performance expression of the dual-site catalyst in PEM applications.

[0067] (2) From the perspective of actual working conditions, the reaction sites of the catalyst working conditions are analyzed, which provides a new perspective for the structural design of the next generation of catalysts. The dual-site supported noble metal catalyst of the present invention successfully achieves the reactivation of the "poisoned" catalyst by introducing structural sites, improves the catalyst utilization rate, and provides a feasible solution for large-scale low-cost hydrogen production. BRIEF DESCRIPTION OF THE DRAWINGS

[0068] In order to more clearly illustrate the specific implementation methods of the present invention or the technical solutions in the prior art, the drawings required for use in the specific implementation methods or the description of the prior art will be briefly introduced below. Obviously, the drawings described below are some implementation methods of the present invention. For ordinary technicians in this field, other drawings can be obtained based on these drawings without paying creative work.

[0069] Figure 1 This is the XPS test chart of the hydrophilic oxide provided in Preparation Example 1 before and after hydroxylation treatment.

[0070] Figure 2 This is a temperature-programmed desorption test diagram of the dual-site supported precious metal catalyst provided in Example 1 and the catalyst provided in Comparative Example 3.

[0071] Figure 3 This is a transmission electron microscopy image of the dual-site supported precious metal catalyst provided in Example 3.

[0072] Figure 4 This is a transmission electron microscopy image of the catalyst provided for Comparative Example 3.

[0073] Figure 5 The PEM water electrolysis performance curve of the membrane electrode prepared by the dual-site supported precious metal catalyst provided by Example 6 and the catalyst provided by Comparative Example 6.

[0074] Figure 6 The in-situ impedance spectra of the membrane electrode prepared by the dual-site supported precious metal catalyst provided by Example 6 and the catalyst provided by Comparative Example 6. DETAILED DESCRIPTION

[0075] Unless otherwise defined herein, scientific and technological terms used in conjunction with the present invention shall have the meanings commonly understood by those of ordinary skill in the art. The meaning and scope of the terms should be clear, however, in the case of any potential ambiguity, the definitions provided herein take precedence over any dictionary or external definitions. In this application, unless otherwise stated, the use of "or" means "and / or". In addition, the use of the term "including" and other forms is non-limiting.

[0076] It should be noted that specific details are described in the following description to facilitate a full understanding of the present invention. However, the present invention can be implemented in a variety of other ways different from those described herein, and those skilled in the art can make similar generalizations without violating the connotation of the present invention. Therefore, the present invention is not limited to the specific embodiments disclosed below.

[0077] The technical solution of the present invention will be clearly and completely described below in conjunction with the embodiments. Obviously, the described embodiments are part of the embodiments of the present invention, rather than all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.

[0078] In a first aspect, the present invention provides a dual-site supported precious metal catalyst, wherein the dual-site supported precious metal catalyst comprises a precious metal oxide and a hydrophilic oxide having a hydroxyl-rich surface and coated in the precious metal oxide.

[0079] In the present invention, the catalyst structure is readjusted and designed from the perspective of actual working conditions to construct a dual-site loaded precious metal catalyst, which is an anode catalyst structure for dual-site synergistic reaction, and uses a hydrophilic oxide with rich hydroxyl groups on the surface as a carrier to load active precious metals. The hydroxyl sites on the surface of the carrier are used as strong adsorption sites for ionomers, which promotes the exposure of active precious metals and improves the performance expression of active sites.

[0080] In the present invention, the dual-site supported noble metal catalyst ionomer adsorption site and active site are separated, and while the exposure of the active site is improved, a stable proton transmission channel is constructed, and finally the catalyst utilization rate and electrolysis efficiency are improved through the efficient and stable catalyst / ionomer interface, and the cost of the PEM electrolysis anode catalyst is reduced. The present invention provides a low-cost, easy-to-operate structure of a catalyst for the PEM electrolysis anode and a preparation method thereof.

[0081] As an optional embodiment, the noble metal oxide is selected from any one of ruthenium oxide, rhodium oxide, iridium oxide or platinum oxide, or a combination of at least two thereof, preferably iridium oxide.

[0082] As an optional embodiment, the loading amount of the precious metal oxide is 10 to 70wt%, for example, it can be 10wt%, 15wt%, 20wt%, 25wt%, 30wt%, 35wt%, 40wt%, 45wt%, 50wt%, 55wt%, 60wt%, 65wt%, 70wt% and the like.

[0083] In the present invention, the noble metal loading can be further adjusted to expose the hydroxyl-rich carrier, which can serve as a strong adsorption site for the ionomer and inhibit the surface adsorption of the noble metal oxide.

[0084] As an optional embodiment, the hydrophilic oxide includes any one of titanium oxide, niobium oxide, tin oxide or silicon oxide, or a combination of at least two thereof.

[0085] As an optional embodiment, the particle size of the hydrophilic oxide is 10nm~1μm, for example, it can be 10nm, 20nm, 40nm, 60nm, 80nm, 100nm, 120nm, 140nm, 160nm, 180nm, 200nm, 250nm, 300nm, 350nm, 400nm, 500nm, 600nm, 700nm, 800nm, 900nm, 1μm, etc.

[0086] As an optional embodiment, the content of hydroxyl groups in the hydrophilic oxide with rich surface hydroxyl groups is 25-75%, for example, it can be 25%, 30%, 35%, 40%, 45%, 50%, 55%, 60%, 65%, 70%, 75%, etc.

[0087] It should be noted that the content here refers to the ratio of the statistical hydroxyl signal to the total oxygen signal on the surface after the mass spectrometry peak signal test of H2O.

[0088] As an optional embodiment, the hydrophilic oxide with rich surface hydroxyl groups is prepared by the following steps:

[0089] The hydrophilic oxide is immersed in a modification solution, and then washed and dried to obtain the hydrophilic oxide with rich hydroxyl groups on the surface; wherein the modification solution includes any one of hydrogen peroxide, a strong base, and a catalyst for Fenton reaction, or a combination of at least two thereof.

[0090] In the present invention, hydroxyl groups are modified on the surface of the hydrophilic oxide by the above-mentioned specific modification method, so that the surface of the dual-site catalyst has more surface hydroxyl groups, which is beneficial to the adsorption of ionomers, thereby constructing a stable proton transport channel.

[0091] As an optional embodiment, the strong base includes any one of sodium hydroxide, potassium hydroxide, lithium hydroxide, cesium hydroxide or rubidium hydroxide, or a combination of at least two thereof.

[0092] As an optional embodiment, the Fenton reaction catalyst includes any one of ferrous chloride, ferrous nitrate or ferrous sulfate, or a combination of at least two of them.

[0093] As an optional embodiment, the mass percentage of the hydrophilic oxide in the modified solution is 0.5-5%, for example, it can be 0.5%, 1%, 1.5%, 2%, 2.5%, 3%, 3.5%, 4%, 4.5%, 5%, etc.

[0094] As an optional embodiment, the soaking temperature is 70-90°C, for example, it can be 70°C, 72°C, 74°C, 75°C, 76°C, 78°C, 80°C, 82°C, 84°C, 85°C, 86°C, 88°C, 90°C, etc., and the soaking time is 20-120min, for example, it can be 20min, 25min, 30min, 35min, 40min, 45min, 50min, 55min, 60min, 65min, 70min, 75min, 80min, 85min, 90min, 95min, 100min, 105min, 110min, 115min, 120min.

[0095] As an optional embodiment, the mass percentage of hydrogen peroxide in the modified solution is 3-30%, for example, it can be 3%, 4%, 6%, 8%, 10%, 12%, 14%, 16%, 18%, 20%, 22%, 24%, 26%, 28%, 30%, etc.

[0096] As an optional embodiment, the mass percentage of the strong base in the modified solution is 1-25%, for example, it can be 1%, 2%, 4%, 6%, 8%, 10%, 12%, 14%, 16%, 18%, 20%, 22%, 24%, 25%, etc.

[0097] As an optional embodiment, the mass percentage of the catalyst for Fenton reaction in the modified solution is 5-50%, for example, it can be 5%, 6%, 8%, 10%, 12%, 14%, 16%, 18%, 20%, 22%, 24%, 26%, 28%, 30%, 32%, 34%, 36%, 38%, 40%, 42%, 44%, 46%, 48%, 50% and the like.

[0098] In a second aspect, the present invention provides a method for preparing a dual-site supported noble metal catalyst as described in the first aspect, wherein the method for preparing a dual-site supported noble metal catalyst comprises the following steps:

[0099] (1) ultrasonically dispersing a hydrophilic oxide having a rich surface hydroxyl group into an alcohol solution, adding a precursor solution of a precious metal dropwise, stirring and drying to obtain a solid mixture;

[0100] (2) mixing and grinding the molten salt and the solid mixture obtained in step (1) to obtain a ground product;

[0101] (3) calcining the ground product obtained in step (2) to obtain a calcined product; then ultrasonically dispersing the calcined product into an aqueous solution, centrifugally washing it with water, and then drying and grinding it to obtain the dual-site supported precious metal catalyst.

[0102] As an optional embodiment, in step (1), the mass ratio of the metal element and the precious metal precursor in the hydrophilic oxide with rich surface hydroxyl groups is 1:(0.15-3.35), for example, it can be 1:0.15, 1:0.5, 1:0.65, 1:1, 1:1.15, 1:1.5, 1:1.65, 1:2, 1:2.15, 1:2.5, 1:2.65, 1:3, 1:3.15, 1:3.35, etc.

[0103] As an optional embodiment, in step (1), the mass volume ratio of the surface hydroxyl-rich hydrophilic oxide and the alcohol solution is 1g:(100-150)mL, for example, it can be 1g:100mL, 1g:110mL, 1g:120mL, 1g:130mL, 1g:140mL, 1g:150mL, etc.

[0104] As an optional embodiment, in step (1), in the precursor solution of the precious metal, the mass volume ratio of the metal precursor and the alcohol solution is 1g:(10-50)mL, for example, it can be 1g:10mL, 1g:15mL, 1g:20mL, 1g:25mL, 1g:30mL, 1g:35mL, 1g:40mL, 1g:45mL, 1g:50mL, etc.

[0105] As an optional embodiment, in step (1), the alcohol solution is isopropanol.

[0106] As an optional embodiment, in step (1), the precursor of the precious metal includes any one of chlororuthenic acid, chlororhodic acid, chloroiridic acid or chloroplatinic acid, or a combination of at least two thereof.

[0107] As an optional embodiment, in step (1), the stirring temperature is 40-60°C, for example, it can be 40°C, 42°C, 44°C, 45°C, 46°C, 48°C, 50°C, 52°C, 54°C, 55°C, 56°C, 58°C, 60°C, etc., and the stirring time is 1-3h, for example, it can be 1h, 1.2h, 1.5h, 1.6h, 1.8h, 2h, 2.2h, 2.4h, 2.5h, 2.6h, 2.8h, 3h, etc.

[0108] As an optional embodiment, in step (1), the drying temperature is 60-90°C, for example, it can be 60°C, 62°C, 64°C, 65°C, 66°C, 68°C, 70°C, 72°C, 74°C, 75°C, 76°C, 78°C, 80°C, 82°C, 84°C, 85°C, 86°C, 88°C, 90°C, etc., and the drying time is 3-5h, for example, it can be 3h, 3.2h, 3.5h, 3.6h, 3.8h, 4h, 4.2h, 4.4h, 4.5h, 4.6h, 4.8h, 5h, etc.

[0109] As an optional embodiment, in step (2), the mass ratio of the molten salt to the solid mixture is (1.43-19.14):1, for example, it can be 1.43:1, 1.5:1, 2:1, 2.5:1, 3:1, 3.5:1, 4:1, 4.5:1, 5:1, 5.5:1, 6:1, 6.5:1, 7:1, 8:1, 9:1, 10:1, 11:1, 12:1, 13:1, 14:1, 15:1, 16:1, 17:1, 18:1, 19:1, 19.14:1, etc., and is preferably (4.78-19.14):1.

[0110] As an optional embodiment, in step (2), the grinding rotation speed is 100-300 rpm, for example, it can be 100 rpm, 150 rpm, 200 rpm, 250 rpm, 300 rpm, etc., and the grinding time is 0.5-2 h, for example, it can be 0.5 h, 0.6 h, 0.8 h, 1 h, 1.2 h, 1.4 h, 1.5 h, 1.6 h, 1.8 h, 2 h, etc.

[0111] As an optional embodiment, in step (2), the particle size of the grinding product obtained by grinding is 300-500nm, for example, it can be 300nm, 320nm, 340nm, 350nm, 360nm, 380nm, 400nm, 420nm, 440nm, 450nm, 460nm, 480nm, 500nm, etc.

[0112] As an optional embodiment, in step (3), the calcination temperature is 250-450°C, for example, it can be 250°C, 260°C, 280°C, 300°C, 320°C, 340°C, 350°C, 360°C, 380°C, 400°C, 420°C, 440°C, 450°C, etc., the calcination time is 0.5-2h, for example, it can be 0.5h, 0.6h, 0.8h, 1h, 1.2h, 1.4h, 1.6h, 1.8h, 2h, etc., and the calcination heating rate is 5-15°C / min, for example, it can be 5°C / min, 6°C / min, 7°C / min, 8°C / min, 9°C / min, 10°C / min, 11°C / min, 12°C / min, 13°C / min, 14°C / min, 15°C / min, etc.

[0113] As an optional embodiment, in step (3), the number of centrifugal washing is 3 to 6 times, for example, 3 times, 4 times, 5 times, 6 times, etc.

[0114] As an optional embodiment, in step (3), the drying temperature is 60-80°C, for example, it can be 60°C, 62°C, 64°C, 65°C, 66°C, 68°C, 70°C, 72°C, 74°C, 75°C, 76°C, 78°C, 80°C, etc., and the drying time is 4-6h, for example, it can be 4h, 4.2h, 4.4h, 4.6h, 4.8h, 5h, 5.2h, 5.4h, 5.6h, 5.8h, 6h, etc.

[0115] As an optional embodiment, in step (3), the grinding rotation speed is 100-300 rpm, for example, it can be 100 rpm, 120 rpm, 140 rpm, 150 rpm, 160 rpm, 180 rpm, 200 rpm, 220 rpm, 240 rpm, 250 rpm, 260 rpm, 280 rpm, 300 rpm, etc., and the grinding time is 0.5-2 h, for example, it can be 0.5 h, 0.6 h, 0.8 h, 1 h, 1.2 h, 1.4 h, 1.6 h, 1.8 h, 2 h, etc.

[0116] As an optional embodiment, in step (3), the particle size of the dual-site supported precious metal catalyst is 10nm to 1μm, for example, it can be 10nm, 20nm, 40nm, 60nm, 80nm, 100nm, 120nm, 140nm, 160nm, 180nm, 200nm, 250nm, 300nm, 350nm, 400nm, 500nm, 600nm, 700nm, 800nm, 900nm, 1μm, etc.

[0117] In a third aspect, the present invention provides a use of a dual-site supported noble metal catalyst as described in the first aspect in the preparation of an anode catalyst for PEM water electrolysis, a membrane electrode for PEM water electrolysis, or an electrolytic cell for PEM water electrolysis.

[0118] In a fourth aspect, the present invention provides a membrane electrode for PEM water electrolysis, comprising a proton exchange membrane and an anode catalyst layer and a cathode catalyst layer arranged on both sides of the proton exchange membrane; wherein the anode catalyst layer comprises a dual-site loaded precious metal catalyst as described in the first aspect.

[0119] As an optional embodiment, the loading amount of the noble metal element in the anode catalyst layer is 0.100 to 1.000 mg / cm 2 , for example, it can be 0.100 mg / cm 2 , 0.200mg / cm 2 , 0.300mg / cm 2 , 0.400mg / cm 2 , 0.500mg / cm 2 , 0.600mg / cm 2 , 0.700mg / cm 2 , 0.800mg / cm 2 、0.900mg / cm 2 , 1.000mg / cm 2 wait.

[0120] As an optional embodiment, the anode catalyst layer further includes an ionomer.

[0121] As an optional embodiment, the ionomer includes any one of perfluorosulfonic acid, sulfonated polyetheretherketone resin or sulfonated trifluorostyrene resin, or a combination of at least two thereof, preferably perfluorosulfonic acid.

[0122] As an optional embodiment, the loading amount of the noble metal element in the cathode catalyst layer is 0.100 to 1.000 mg / cm 2 , for example, it can be 0.100 mg / cm 2 , 0.200mg / cm 2 , 0.300mg / cm 2 , 0.400mg / cm 2 , 0.500mg / cm 2 , 0.600mg / cm 2 , 0.700mg / cm 2 , 0.800mg / cm 2 、0.900mg / cm 2 , 1.000mg / cm 2wait.

[0123] As an optional embodiment, the proton exchange membrane is a 115 proton exchange membrane.

[0124] In a fifth aspect, the present invention provides a method for preparing a membrane electrode for PEM water electrolysis according to the fourth aspect, the method for preparing a membrane electrode for PEM water electrolysis comprising the following steps:

[0125] The dual-site supported noble metal catalyst, ionomer solution, water and alcohol are mixed, stirred and dispersed, and degassed after ball milling to obtain an anode catalyst layer slurry;

[0126] Applying the anode catalyst layer slurry to one side of the transfer substrate, and after drying, forming the anode catalyst layer;

[0127] Applying the cathode catalyst layer slurry to the other side of the transfer substrate, and after drying, forming the cathode catalyst layer;

[0128] The anode catalyst layer and the cathode catalyst layer are respectively transferred to both sides of the proton exchange membrane by hot pressing transfer to obtain the PEM membrane electrode for water electrolysis.

[0129] As an optional embodiment, the dual-site supported precious metal catalyst accounts for 15-40% of the total mass of the anode catalyst layer slurry, for example, it can be 15%, 16%, 18%, 20%, 22%, 24%, 25%, 26%, 28%, 30%, 32%, 34%, 35%, 36%, 38%, 40% and the like.

[0130] As an optional embodiment, the ionomer solution is 5-40% of the mass of the dual-site supported precious metal catalyst, for example, it can be 5%, 6%, 8%, 10%, 12%, 15%, 16%, 18%, 20%, 22%, 24%, 25%, 26%, 28%, 30%, 32%, 34%, 35%, 36%, 38%, 40%, etc.

[0131] As an optional implementation, the solid content of the ionomer solution is 15-20wt%, for example, 15wt%, 16wt%, 17wt%, 18wt%, 19wt%, 20wt% and the like.

[0132] As an optional embodiment, the alcohol is a C1-C8 monohydric liquid alcohol and / or a C1-C8 polyhydric liquid alcohol.

[0133] As an optional embodiment, the alcohol is selected from any one of ethanol, n-propanol, isopropanol or propylene glycol, or a combination of at least two thereof.

[0134] As an optional embodiment, the mass ratio of water to alcohol is (5-8):(2-5), for example, it can be 5:5, 6:4, 7:3, 8:2, etc.

[0135] As an optional embodiment, the ball milling conditions include: 2.0-4.5 mm ZrO2 ball milling beads, constant temperature ball milling at 15-25°C, a rotation speed of 300-1000 rpm, and a time of 2-12 hours.

[0136] As an optional embodiment, the particle size of the ZrO2 ball milling beads is 2.0-4.5 mm, for example, it can be 2.0 mm, 2.2 mm, 2.4 mm, 2.5 mm, 2.6 mm, 2.8 mm, 3 mm, 3.2 mm, 3.4 mm, 3.5 mm, 3.6 mm, 3.8 mm, 4 mm, 4.2 mm, 4.4 mm, 4.5 mm, etc.

[0137] As an optional embodiment, the ball milling temperature is 15-25°C, for example, it can be 15°C, 16°C, 17°C, 18°C, 19°C, 20°C, 21°C, 22°C, 23°C, 24°C, 25°C, etc.

[0138] As an optional embodiment, the rotation speed of the ball mill is 300-1000rpm, for example, it can be 300rpm, 350rpm, 400rpm, 450rpm, 500rpm, 550rpm, 600rpm, 650rpm, 700rpm, 750rpm, 800rpm, 850rpm, 900rpm, 950rpm, 1000rpm, etc.

[0139] As an optional embodiment, the ball milling time is 2 to 12 hours, for example, it can be 2h, 2.5h, 3h, 3.5h, 4h, 4.5h, 5h, 5.5h, 6h, 6.5h, 7h, 7.5h, 8h, 8.5h, 9h, 9.5h, 10h, 10.5h, 11h, 11.5h, 12h, etc.

[0140] In a sixth aspect, the present invention provides an electrolytic cell for PEM water electrolysis, wherein the electrolytic cell for PEM water electrolysis comprises the membrane electrode for PEM water electrolysis described in the fourth aspect.

[0141] The present invention is further described below by way of examples. Unless otherwise specified, the materials in the examples are prepared according to existing methods or directly purchased from the market.

[0142] Preparation Example 1

[0143] This preparation example provides a niobium oxide with a surface rich in hydroxyl groups, and the niobium oxide with a surface rich in hydroxyl groups is prepared by the following steps:

[0144] 1.0 g of niobium oxide was soaked in hydrogen peroxide (100 mL, 30 wt% H2O2) at 80°C for 30 min, then washed with ionized water for several times, and then dried in an oven at 80°C to obtain niobium oxide with rich surface hydroxyl groups (hydroxyl content of 53.2%).

[0145] Preparation Example 2

[0146] This preparation example provides a tin oxide with a surface rich in hydroxyl groups, and the tin oxide with a surface rich in hydroxyl groups is prepared by the following steps:

[0147] 1.0 g of tin oxide was soaked in hydrogen peroxide (80 mL, 20 wt% H2O2) at 80°C for 1 h, then washed several times with ionized water, and dried in an oven at 80°C to obtain tin oxide with a surface rich in hydroxyl groups (hydroxyl content of 42.7%).

[0148] Preparation Example 3

[0149] This preparation example provides a hydroxyl-rich silicon dioxide on the surface, and the hydroxyl-rich silicon dioxide on the surface is prepared by the following steps:

[0150] 1.0 g of silica was soaked in hydrogen peroxide (50 mL, 10 wt% H2O2) at 80°C for 1.5 h, then washed several times with ionized water, and dried in an oven at 80°C to obtain silica with a surface rich in hydroxyl groups (hydroxyl content of 48.6%).

[0151] Preparation Example 4

[0152] This preparation example provides a titanium dioxide with a hydroxyl-rich surface, and the titanium dioxide with a hydroxyl-rich surface is prepared by the following steps:

[0153] 1.0 g of titanium dioxide was soaked in hydrogen peroxide (100 mL, 30 wt% H2O2) at 80°C for 2 h, then washed with ionized water for several times, and then dried in an oven at 80°C to obtain titanium dioxide with a hydroxyl-rich surface (hydroxyl content of 72.4%).

[0154] Preparation Example 5

[0155] This preparation example provides a niobium oxide with a surface rich in hydroxyl groups, which is different from Preparation Example 1 only in that 20 wt % of NaOH is further added to the hydrogen peroxide, and the other steps are completely consistent with Preparation Example 1.

[0156] Preparation Example 6

[0157] This preparation example provides a niobium oxide with a surface rich in hydroxyl groups, which is different from Preparation Example 1 only in that 10 wt % of FeCl2 is further added to the hydrogen peroxide, and the other steps are completely consistent with Preparation Example 1.

[0158] Test Example 1

[0159] XPS Test

[0160] Test samples: hydrophilic oxides with rich surface hydroxyl groups provided in Preparation Examples 1 to 6, and the corresponding hydrophilic oxides before hydroxyl-rich treatment in each example.

[0161] Test method: XPS test, observe and count the proportion of hydroxyl peak.

[0162] The test results are shown in Table 1 and Figure 1 As shown:

[0163] Table 1

[0164]

[0165] From Table 1 and Figure 1 As shown, after the hydrophilic oxide is treated with hydroxylation, the proportion of surface hydroxyl functional groups (the second peak) is significantly increased.

[0166] Example 1

[0167] This embodiment provides a dual-site supported noble metal catalyst, which is prepared by the following steps:

[0168] (1) After ultrasonically dispersing 1 g of the hydroxyl-rich niobium oxide provided in Preparation Example 1 (average particle size of 10 nm) into 100 mL of isopropanol solution, 100 mL of H2IrCl6 solution (concentration of 0.015 g / mL) was added dropwise and stirred for 1 h to form a uniformly dispersed solution. The solution was then dried in an oven at 60°C for 5 h to form a solid mixture.

[0169] (2) The solid mixture with a mass ratio of 4.75:1 and NaNO3 were ground together (rotation speed 100 rpm, grinding for 2 h) to obtain a grinding product (average particle size of 100 nm).

[0170] (3) The ground product is calcined at 250°C for 2 h, with a heating rate of preferably 5°C / min; naturally cooled to room temperature, ultrasonically dispersed in an aqueous solution, centrifuged and washed with water 6 times to remove excess impurity salts, dried in an oven at 70°C for 6 h, and ground evenly (rotating speed 100 rpm, grinding for 2 h) to obtain a dual-site supported precious metal catalyst (average particle size of 12 nm).

[0171] Example 2

[0172] This embodiment provides a dual-site supported noble metal catalyst, which is prepared by the following steps:

[0173] (1) After ultrasonically dispersing 1 g of the hydroxyl-rich niobium oxide provided in Preparation Example 1 (average particle size of 50 nm) into 125 mL of isopropanol solution, 60 mL of H2IrCl6 solution (concentration of 0.062 g / mL) was added dropwise and stirred for 2 h to form a uniformly dispersed solution. The mixture was then dried in an oven at 75°C for 4 h to form a solid mixture.

[0174] (2) The solid mixture with a mass ratio of 10:1 and NaNO3 were ground together (rotation speed 200 rpm, grinding for 1 h) to obtain a grinding product (average particle size of 100 nm).

[0175] (3) The ground product was calcined at 350°C for 1 h, with a heating rate of preferably 10°C / min; naturally cooled to room temperature, ultrasonically dispersed in an aqueous solution, centrifuged and washed 4 times to remove excess impurity salts, dried in an oven at 80°C for 4 h, and ground evenly (rotating speed 200 rpm, grinding for 1 h) to obtain a dual-site supported precious metal catalyst (average particle size 55 nm).

[0176] Example 3

[0177] This embodiment provides a dual-site supported noble metal catalyst, which is prepared by the following steps:

[0178] (1) After ultrasonically dispersing 1 g of the hydroxyl-rich niobium oxide provided in Preparation Example 1 (average particle size of 100 nm) into 150 mL of isopropanol solution, 50 mL of H2IrCl6 solution (concentration of 0.049 g / mL) was added dropwise and stirred for 2 h to form a uniformly dispersed solution. The solution was then dried in an oven at 90°C for 3 h to form a solid mixture.

[0179] (2) The solid mixture with a mass ratio of 19.14:1 and NaNO3 were ground together (rotation speed 300 rpm, grinding 0.5 h) to obtain a grinding product (average particle size of 300 nm).

[0180] (3) The ground product is calcined at 450°C for 0.5h, with a heating rate of preferably 15°C / min; naturally cooled to room temperature, ultrasonically dispersed in an aqueous solution, centrifuged and washed with water three times to remove excess impurity salts, dried in an oven at 60°C for 6h, and ground evenly (rotating speed 300rpm, grinding 0.5h), to obtain a dual-site supported precious metal catalyst (average particle size of 104nm).

[0181] Example 4

[0182] This embodiment provides a dual-site supported precious metal catalyst, which differs from Example 1 only in that the surface hydroxyl-rich niobium oxide provided in Preparation Example 1 is replaced by an equal amount of surface hydroxyl-rich tin oxide provided in Preparation Example 2, and the other steps are exactly the same as Example 1.

[0183] Example 5

[0184] This embodiment provides a dual-site supported precious metal catalyst, which differs from Example 1 only in that the surface hydroxyl-rich niobium oxide provided in Preparation Example 1 is replaced by an equal amount of surface hydroxyl-rich silicon dioxide provided in Preparation Example 3, and the other steps are exactly the same as Example 1.

[0185] Example 6

[0186] This embodiment provides a dual-site supported precious metal catalyst, which differs from Example 1 only in that the surface hydroxyl-rich niobium oxide provided in Preparation Example 1 is replaced by an equal amount of surface hydroxyl-rich titanium dioxide provided in Preparation Example 4, and the other steps are exactly the same as Example 1.

[0187] Example 7

[0188] This embodiment provides a dual-site supported precious metal catalyst, which is different from Example 1 only in that the surface hydroxyl-rich niobium oxide provided in Preparation Example 1 is replaced by an equal amount of surface hydroxyl-rich niobium oxide provided in Preparation Example 5, and the other steps are exactly the same as Example 1.

[0189] Example 8

[0190] This embodiment provides a dual-site supported precious metal catalyst, which is different from Example 1 only in that the surface hydroxyl-rich niobium oxide provided in Preparation Example 1 is replaced by an equal amount of surface hydroxyl-rich niobium oxide provided in Preparation Example 6, and the other steps are exactly the same as Example 1.

[0191] Example 9

[0192] This embodiment provides a dual-site supported precious metal catalyst, which is different from Embodiment 1 only in that the H2IrCl6 solution is replaced by an equal amount of RuCl3 solution, and the other steps are exactly the same as Embodiment 1.

[0193] Comparative Example 1

[0194] This comparative example provides a catalyst, which is iridium oxide.

[0195] Comparative Example 2

[0196] This comparative example provides a catalyst, which is ruthenium oxide.

[0197] Comparative Example 3

[0198] This comparative example provides a catalyst, which is different from Example 1 only in that the surface hydroxyl-rich niobium oxide provided in Preparation Example 1 is replaced by commercial niobium oxide that has not been treated with hydroxyl enrichment, and the other steps are completely consistent with Example 1.

[0199] Comparative Example 4

[0200] This comparative example provides a catalyst, which is different from Example 4 only in that the surface hydroxyl-rich tin oxide provided in Preparation Example 2 is replaced by commercial tin oxide that has not been treated with hydroxyl enrichment, and the other steps are completely consistent with Example 4.

[0201] Comparative Example 5

[0202] This comparative example provides a catalyst, which is different from Example 5 only in that the surface hydroxyl-rich silica provided in Preparation Example 3 is replaced by commercial silica that has not been treated with hydroxyl enrichment, and the other steps are exactly the same as Example 5.

[0203] Comparative Example 6

[0204] This comparative example provides a catalyst, which is different from Example 6 only in that the surface hydroxyl-rich titanium dioxide provided in Preparation Example 4 is replaced by commercial titanium dioxide that has not been treated with hydroxyl enrichment, and the other steps are completely consistent with Example 6.

[0205] Test Example 2

[0206] Temperature programmed desorption test

[0207] Test samples: the dual-site supported noble metal catalysts provided in Examples 1 to 9 and the catalysts provided in Comparative Examples 1 to 6.

[0208] Test method: programmed temperature desorption test, counting the mass spectrum peak signal area of ​​H2O.

[0209] The test results are shown in Table 2 and Figure 2 As shown:

[0210] Table 2

[0211]

[0212]

[0213] From Table 2 and Figure 2 As shown, the peak temperature of H2O of the dual-site supported precious metal catalyst of the present invention is 341-364°C, and the mass spectrum peak signal area of ​​H2O is 3.9E-8-6.2E-8; this fully illustrates that the dual-site catalyst of the present invention has more surface hydroxyl groups, which is beneficial to the adsorption of ionomers and the construction of a stable proton transmission channel.

[0214] also, Figure 3 This is a transmission electron microscopy image of the dual-site supported precious metal catalyst provided in Example 3. Figure 4 The transmission electron microscope image of the catalyst provided for Comparative Example 3. Figure 3 and Figure 4 As shown in the comparison, a large amount of ionomers are adsorbed on the surface of the traditional catalyst iridium oxide particles, with a thickness of about 5 to 10 nm, causing serious poisoning of the catalyst performance expression. The active sites of the dual-site catalyst are basically exposed, achieving a higher active area.

[0215] Application Example 1

[0216] This application example provides a PEM membrane electrode for water electrolysis, and the PEM membrane electrode for water electrolysis is prepared by the following steps:

[0217] (a) Deionized water, PEM water electrolysis anode catalyst, ionomer solution and alcohol are added to a glass bottle in sequence, the glass bottle is placed on a magnetic stirrer, after stirring and dispersing, the solution is transferred to a ball milling jar containing ball milling beads, and ball milling is performed under constant temperature;

[0218] The anode catalyst is the dual-site supported noble metal catalyst provided in Example 1, and the mass of the catalyst accounts for 25wt% of the total mass of the slurry; the ionomer solution is a perfluorosulfonic acid solution, and the mass of the ionomer solution is 20wt% of the mass of the catalyst; the alcohol is isopropanol, and the mass ratio of the added deionized water to the total liquid alcohol is 6:4;

[0219] The ball milling conditions are: 3.5 mm ZrO2 ball milling beads, constant temperature ball milling at 20°C, a rotation speed of 650 rpm, and a time of 7 hours.

[0220] (b) After ball milling and dispersion, the slurry is mixed and degassed using a degassing machine to obtain an anode catalyst layer slurry.

[0221] (c) Coating on PTFE membrane using a slot coater (loading 0.500 mg Ir / cm 2 ).

[0222] (d) After drying, XRF is used to detect whether the average iridium loading in the catalyst coating meets the standard.

[0223] (e) The mixture was then coated on a PTFE membrane with a loading of 0.3 mg Pt / cm 2 The cathode catalyst layer and 115 proton exchange membrane were prepared into catalyst coated membrane (CCM) by hot pressing transfer.

[0224] Application Example 2

[0225] This application example provides a membrane electrode for PEM water electrolysis. The only difference from Application Example 1 is that the dual-site loaded precious metal catalyst provided in Example 1 is replaced with an equal-loaded dual-site loaded precious metal catalyst provided in Example 2. The other steps are exactly the same as those in Application Example 1.

[0226] Application Example 3

[0227] This application example provides a membrane electrode for PEM water electrolysis. The only difference from Application Example 1 is that the dual-site loaded precious metal catalyst provided in Example 1 is replaced with a dual-site loaded precious metal catalyst provided in Example 3 with an equal loading. The other steps are exactly the same as those in Application Example 1.

[0228] Application Example 4

[0229] This application example provides a membrane electrode for PEM water electrolysis. The only difference from Application Example 1 is that the dual-site loaded precious metal catalyst provided in Example 1 is replaced with a dual-site loaded precious metal catalyst provided in Example 4 with an equal loading, and the other steps are exactly the same as those in Application Example 1.

[0230] Application Example 5

[0231] This application example provides a membrane electrode for PEM water electrolysis. The only difference from Application Example 1 is that the dual-site loaded precious metal catalyst provided in Example 1 is replaced with a dual-site loaded precious metal catalyst provided in Example 5 with an equal loading. The other steps are exactly the same as those in Application Example 1.

[0232] Application Example 6

[0233] This application example provides a membrane electrode for PEM water electrolysis. The only difference from Application Example 1 is that the dual-site loaded precious metal catalyst provided in Example 1 is replaced with a dual-site loaded precious metal catalyst provided in Example 6 with an equal loading, and the other steps are exactly the same as those in Application Example 1.

[0234] Application Example 7

[0235] This application example provides a membrane electrode for PEM water electrolysis. The only difference from Application Example 1 is that the dual-site loaded precious metal catalyst provided in Example 1 is replaced with a dual-site loaded precious metal catalyst provided in Example 7 with an equal loading. The other steps are exactly the same as those in Application Example 1.

[0236] Application Example 8

[0237] This application example provides a membrane electrode for PEM water electrolysis. The only difference from Application Example 1 is that the dual-site loaded precious metal catalyst provided in Example 1 is replaced with a dual-site loaded precious metal catalyst provided in Example 8 with an equal loading, and the other steps are exactly the same as those in Application Example 1.

[0238] Application Example 9

[0239] This application example provides a membrane electrode for PEM water electrolysis. The only difference from Application Example 1 is that the dual-site loaded precious metal catalyst provided in Example 1 is replaced with a dual-site loaded precious metal catalyst provided in Example 9 with an equal loading, and the other steps are exactly the same as those in Application Example 1.

[0240] Comparative application example 1

[0241] This application example provides a membrane electrode for PEM water electrolysis. The only difference from Application Example 1 is that the dual-site loaded precious metal catalyst provided in Example 1 is replaced with a catalyst provided in Comparative Example 1 with an equal loading amount, and the other steps are exactly the same as those in Application Example 1.

[0242] Comparative Application Example 2

[0243] This application example provides a membrane electrode for PEM water electrolysis. The only difference from Application Example 1 is that the dual-site loaded precious metal catalyst provided in Example 1 is replaced with a catalyst provided in Comparative Example 2 with an equal loading amount. The other steps are exactly the same as those in Application Example 1.

[0244] Comparative Application Example 3

[0245] This application example provides a membrane electrode for PEM water electrolysis. The only difference from Application Example 1 is that the dual-site loaded precious metal catalyst provided in Example 1 is replaced with a catalyst provided in Comparative Example 3 with an equal loading amount. The other steps are exactly the same as those in Application Example 1.

[0246] Comparative Application Example 4

[0247] This application example provides a membrane electrode for PEM water electrolysis. The only difference from Application Example 1 is that the dual-site loaded precious metal catalyst provided in Example 1 is replaced with a catalyst provided in Comparative Example 4 with an equal loading amount. The other steps are exactly the same as those in Application Example 1.

[0248] Comparative Application Example 5

[0249] This application example provides a membrane electrode for PEM water electrolysis. The only difference from Application Example 1 is that the dual-site loaded precious metal catalyst provided in Example 1 is replaced with a catalyst provided in Comparative Example 5 with an equal loading amount. The other steps are exactly the same as those in Application Example 1.

[0250] Comparative Application Example 6

[0251] This application example provides a membrane electrode for PEM water electrolysis. The only difference from Application Example 1 is that the dual-site loaded precious metal catalyst provided in Example 1 is replaced with a catalyst provided in Comparative Example 6 with an equal loading amount. The other steps are exactly the same as those in Application Example 1.

[0252] Test Example 3

[0253] Multi-channel device performance testing

[0254] Test samples: PEM membrane electrodes for water electrolysis provided in Application Examples 1 to 9, and PEM membrane electrodes for water electrolysis provided in Comparative Application Examples 1 to 6.

[0255] Test method:

[0256] (1) Assembly of electrolytic cell: Assemble the above samples into an electrolytic cell in the order of insulating end plate, cathode plate, 0.15 mm gasket, carbon paper, membrane electrode (CCM), 2.05 mm gasket, titanium felt, titanium mesh and anode plate. Tighten the electrolytic cell diagonally with a torque wrench (3 N·m) and clamp the electrode clamp.

[0257] (2) Polarization performance test method: During the PEMWE working condition test, the program is set to record the current density from the low current density of 0.025A / cm 2 The cell pressure of the electrolytic cell is plotted as a function of the current density at a high current density of 6 A / cm2.

[0258] (3) Under the PEMWE working conditions, the electrochemical stability test was carried out by chronopotentiometry. 2 The stability test was carried out for 180 hours. During the stability test, the real-time current and voltage values ​​were recorded.

[0259] The test results are shown in Tables 3 and 4 below. Figure 5-6 As shown:

[0260] Table 3

[0261]

[0262]

[0263] Table 4

[0264]

[0265]

[0266] As shown in Tables 3 to 4 above and Figure 5-6 As shown, the dual-site catalyst has a significantly smaller charge transfer impedance, proving that it has faster electrochemical oxygen evolution reaction kinetics due to the synergistic reaction pathway of charge-mass separation.

[0267] In summary, the present invention readjusts and designs the catalyst structure from the perspective of actual working conditions, constructs an anode catalyst structure with dual-site synergistic reaction, separates the ionomer adsorption site from the active site, improves the exposure of the active site, and constructs a stable proton transmission channel. Ultimately, the catalyst utilization rate and electrolysis efficiency are improved through an efficient and stable catalyst / ionomer interface, thereby reducing the cost of PEM water electrolysis anode catalyst.

[0268] Finally, it should be noted that the above embodiments are only used to illustrate the technical solutions of the present invention, rather than to limit it. Although the present invention has been described in detail with reference to the aforementioned embodiments, those skilled in the art should understand that they can still modify the technical solutions described in the aforementioned embodiments, or replace some or all of the technical features therein with equivalents. However, these modifications or replacements do not cause the essence of the corresponding technical solutions to deviate from the scope of the technical solutions of the embodiments of the present invention.

Claims

1. A dual-site supported noble metal catalyst, characterized in that: The dual-site supported noble metal catalyst comprises a noble metal oxide and a hydrophilic oxide with a surface rich in hydroxyl groups and coated in the noble metal oxide.

2. The dual-site supported noble metal catalyst according to claim 1, characterized in that: The noble metal oxide is selected from any one or a combination of at least two of ruthenium oxide, rhodium oxide, iridium oxide or platinum oxide, preferably iridium oxide; Preferably, the loading amount of the noble metal oxide is 10 to 70 wt %; Preferably, the hydrophilic oxide comprises any one or a combination of at least two of titanium oxide, niobium oxide, tin oxide or silicon oxide; Preferably, the particle size of the hydrophilic oxide is 10 nm to 1 μm; Preferably, the content of hydroxyl groups in the hydrophilic oxide with rich surface hydroxyl groups is 25-75%; Preferably, the hydrophilic oxide with rich surface hydroxyl groups is prepared by the following steps: The hydrophilic oxide is immersed in a modification solution, and then washed and dried to obtain the hydrophilic oxide with rich hydroxyl groups on the surface; wherein the modification solution comprises any one of hydrogen peroxide, a strong base, and a catalyst for Fenton reaction, or a combination of at least two thereof; Preferably, the strong base includes any one or a combination of at least two of sodium hydroxide, potassium hydroxide, lithium hydroxide, cesium hydroxide or rubidium hydroxide; Preferably, the Fenton reaction catalyst comprises any one of ferrous chloride, ferrous nitrate or ferrous sulfate, or a combination of at least two thereof; Preferably, the mass percentage of the hydrophilic oxide in the modified solution is 0.5-5%; Preferably, the soaking temperature is 70-90°C, and the soaking time is 20-120 minutes; Preferably, the mass percentage of hydrogen peroxide in the modified solution is 3 to 30%; Preferably, the mass percentage of the strong base in the modified solution is 1 to 25%; Preferably, the mass percentage of the Fenton reaction catalyst in the modified solution is 5 to 50%.

3. A method for preparing the dual-site supported noble metal catalyst according to claim 1 or 2, characterized in that: The preparation method of the dual-site supported noble metal catalyst comprises the following steps: (1) ultrasonically dispersing a hydrophilic oxide having a rich surface hydroxyl group into an alcohol solution, adding a precursor solution of a precious metal dropwise, stirring and drying to obtain a solid mixture; (2) mixing and grinding the molten salt and the solid mixture obtained in step (1) to obtain a ground product; (3) calcining the ground product obtained in step (2) to obtain a calcined product; then ultrasonically dispersing the calcined product into an aqueous solution, centrifugally washing it with water, and then drying and grinding it to obtain the dual-site supported precious metal catalyst.

4. The method for preparing a dual-site supported noble metal catalyst according to claim 3, characterized in that: In step (1), the mass ratio of the metal element in the hydrophilic oxide with rich surface hydroxyl groups to the noble metal in the precursor is 1:(0.15-3.35); Preferably, in step (1), the mass volume ratio of the hydrophilic oxide with rich surface hydroxyl groups to the alcohol solution is 1 g: (100-150) mL; Preferably, in step (1), in the precursor solution of the noble metal, the mass volume ratio of the metal precursor to the alcohol solution is 1 g: (10-50) mL; Preferably, in step (1), the alcohol solution is isopropanol; Preferably, in step (1), the precursor of the precious metal comprises any one of chlororuthenic acid, chlororhodic acid, chloroiridic acid, ruthenium trichloride, iridium acetate, iridium acetylacetonate or chloroplatinic acid, or a combination of at least two thereof; Preferably, in step (1), the stirring temperature is 40 to 60° C., and the stirring time is 1 to 3 hours; Preferably, in step (1), the drying temperature is 60 to 90° C., and the drying time is 3 to 5 hours; Preferably, in step (2), the mass ratio of the molten salt to the solid mixture is (1.43-19.14):1, preferably (4.78-19.14):1; Preferably, in step (2), the grinding speed is 100 to 300 rpm, the grinding time is 0.5 to 2 h; the particle size of the grinding product obtained by the grinding is 300 to 500 nm; Preferably, in step (3), the calcination temperature is 250-450°C, the calcination time is 0.5-2h, and the calcination heating rate is 5-15°C / min; Preferably, in step (3), the number of centrifugal washing is 3 to 6 times; Preferably, in step (3), the drying temperature is 60 to 80° C., and the drying time is 4 to 6 hours; Preferably, in step (3), the grinding speed is 100 to 300 rpm, and the grinding time is 0.5 to 2 h; Preferably, in step (3), the particle size of the dual-site supported noble metal catalyst is 10 nm to 1 μm.

5. Use of the dual-site supported noble metal catalyst according to claim 1 or 2 in the preparation of an anode catalyst for PEM water electrolysis, a membrane electrode for PEM water electrolysis or an electrolytic cell for PEM water electrolysis.

6. A membrane electrode for PEM water electrolysis, characterized in that: The membrane electrode for PEM water electrolysis comprises a proton exchange membrane and an anode catalyst layer and a cathode catalyst layer arranged on both sides of the proton exchange membrane; wherein the anode catalyst layer comprises the dual-site supported precious metal catalyst according to claim 1 or 2.

7. The membrane electrode for PEM water electrolysis according to claim 6, characterized in that: The loading of the noble metal element in the anode catalyst layer is 0.100-1.000 mg / cm 2 ; Preferably, the anode catalyst layer further comprises an ionomer; Preferably, the ionomer comprises any one or a combination of at least two of perfluorosulfonic acid, sulfonated polyetheretherketone resin or sulfonated trifluorostyrene resin, preferably perfluorosulfonic acid; Preferably, the loading of the noble metal element in the cathode catalyst layer is 0.100-1.000 mg / cm 2 ; Preferably, the proton exchange membrane is a 115 proton exchange membrane.

8. A method for preparing a membrane electrode for PEM water electrolysis according to claim 6 or 7, characterized in that: The preparation method of the PEM membrane electrode for water electrolysis comprises the following steps: The dual-site supported noble metal catalyst, ionomer solution, water and alcohol are mixed, stirred and dispersed, and degassed after ball milling to obtain an anode catalyst layer slurry; Applying the anode catalyst layer slurry to one side of the transfer substrate, and after drying, forming the anode catalyst layer; Applying the cathode catalyst layer slurry to the other side of the transfer substrate, and after drying, forming the cathode catalyst layer; The anode catalyst layer and the cathode catalyst layer are respectively transferred to both sides of the proton exchange membrane by hot pressing transfer to obtain the PEM membrane electrode for water electrolysis.

9. The method for preparing a membrane electrode for PEM water electrolysis according to claim 8, characterized in that: The dual-site supported noble metal catalyst accounts for 15-40% of the total mass of the anode catalyst layer slurry; Preferably, the ionomer solution is 5 to 40% of the mass of the dual-site supported noble metal catalyst; Preferably, the solid content of the ionomer solution is 15-20 wt%; Preferably, the alcohol is a C1-C8 monohydric liquid alcohol and / or a C1-C8 polyhydric liquid alcohol; Preferably, the alcohol is selected from any one or a combination of at least two of ethanol, n-propanol, isopropanol or propylene glycol; Preferably, the mass ratio of water to alcohol is (5-8):(2-5); Preferably, the ball milling conditions include: 2.0-4.5 mm ZrO2 ball milling beads, constant temperature ball milling at 15-25°C, a rotation speed of 300-1000 rpm, and a time of 2-12 hours.

10. A PEM electrolytic cell for water electrolysis, characterized in that: The PEM water electrolysis electrolysis cell comprises the PEM water electrolysis membrane electrode according to claim 6 or 7.

Citation Information

Patent Citations

  • Metal Ionophores in PEM Membranes

    CN103682392A

  • Amorphous titanium dioxide / nano iridium oxide / porous silicon anode and preparing method thereof

    CN106283104A

  • Anode catalyst for water electrolysis hydrogen production by taking transition metal doped titanium oxide as a carrier and preparation method of anode catalyst

    CN111266110A

  • Supported noble metal oxide and preparation method thereof

    CN116371403A

  • Modified boron nitride nanotube composite proton exchange membrane and preparation method thereof

    CN116722188A